Negative Symptom Interventions in Youth at Risk of Psychosis: A Systematic Review and Network Meta-analysis. (24th October 2017) - Devoe, Daniel J; Peterson, Aaron; Addington, Jean
Abstract: Objective: Youth at clinical high risk (CHR) for psychosis often demonstrate significant negative symptoms, which have been reported to be predictive of conversion to psychosis and a reduced quality of life but treatment options for negative symptoms remain inadequate. Therefore, we conducted a systematic review and network meta-analysis of all intervention studies examining negative symptom outcomes in youth at CHR for psychosis. Method: The authors searched PsycINFO, Medline, Embase, CINAHL, and EBM from inception to December 2016. Studies were selected if they included any intervention that reported follow-up negative symptoms in youth at CHR for psychosis. Treatment comparisons were evaluated using both pairwise and network meta-analyses. Due to the differences in negative symptom scales the effect sizes were reported as the standardized mean difference (SMD). Results: Of 3027 citations, 32 studies met our inclusion criteria, including a total of 2463 CHR participants. The null hypothesis was not rejected for any of the 11 treatments. N -methyl-D-aspartate-receptor (NMDAR) modulators trended toward a significant reduction in negative symptoms compared to placebo (SMD = −0.54; 95% CI = −1.09 to 0.02; I 2 = 0%, P = .06). In respective order of descending effectiveness as per the treatment hierarchy, NMDAR modulators were more effective than family therapy, need-based interventions, risperidone, amisulpride, cognitive behavioral therapy, omega-3, olanzapine, supportive therapy, and integrated psychological interventions. Conclusions: Efficacy and effectiveness were not confirmed for any negative symptom treatment. Many studies had small samples and the majority were not designed to target negative symptoms.